Socially constructed meanings of Impucuko in a comparative historical analysis - Sigenu, Zimingonaphakade (Department of Sociology, 2022)
Sociological analysis of African societies has tended to rely on Western concepts and theories while neglecting indigenous conceptualisations and explanations of social phenomena. Guided by social constructionism and hermeneutics, this thesis seeks to respond to this by investigating the socially constructed meanings of impucuko (dictionary translation: civilisation) and associated terms by isiXhosa-speaking professionals at the turn of the 20th century and then again at the turn of the 21st century, exploring the changes and continuities in the meanings over the 100-year period. Documentary sources from the isiXhosa literary archive, a sample of contemporary isiXhosa newspapers and in-depth interviews are utilised as part of the qualitative research approach to explore the social construction of meaning. The different meanings of impucuko that emerge from the inquiry include an understanding of the concept as: • enlightening knowledge • inkqubela phambili (progress) • detachment from inkcubeko (cultural heritage) • reimagined as a system of development that uplifts. This thesis demonstrates the practice of endogeneity by taking a single isiXhosa term, impucuko (and associated words), and demonstrating how endogeneity works organically in the process of the social construction of meanings in the vernacular by African sociolinguistic groupings. It highlights the relationship between socio-cultural context and meaning construction. The study challenges the hegemony assumed by western conceptual tools and the English language in academic knowledge production. Furthermore, the thesis shows an innovative method of developing critical conceptual tools that centre African perspectives.